THE EFFECT OF SERUM 25-HYDROXY VITAMIN D ON VISUAL FIELDS IN MODERATE - HIGH MYOPIA - Simbolon, Ahmad Musa; Sitepu, Bobby Ramses Erguna; Lubis, Rodiah Rahmawaty (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesMyopia is a visual impairment problem that constantly increases, causing global health problemsand economic burdens. Previous studies have concluded that vitamin D deficiency is associated withdecreased visual acuity and visual function. To determine the relationship between serum 25(OH)Dlevels and visual fields in moderate to high myopia MethodsThis study was an observational analytic study with a cross-sectional design. Visual function testsperformed were visual acuity test, Humphrey visual field analyzer, and ELISA test for serum25(OH)D. ResultsThe study consisted of 50 subjects with moderate to high myopia with 39 subjects was females (60%)and mean age of 26.62±3.70 years. The distribution of moderate myopia and high myopia was 30%and 20% with a mean spherical equivalent of -5.11±1.54 D. Twenty four subjects (48%) had serum25(OH)D deficiency, 1 subject (2%) had insufficiency of serum 25(OH)D with an average level of44.56±41.45 ng/ml. Fischer's Exact analysis on the right eye revealed 7 subjects (29.2%) had serum25(OH)D deficiency and insufficiency with visual field defect (p=0.001). On the left eye, 6 subjects(25%) had serum 25(OH)D deficiency and insufficiency with visual field defect (p=0.132). ConclusionThere was statistically significant relationship between serum 25(OH)D levels and visual field inmoderate to high myopia in one eye.